Effect of chemical fertilizers on growth, yield and quality of fennel (Foeniculum vulgare Miller) - K K Thakral, Hans Raj (Journal of Spices and Aromatic Crops, 2008)
A field experiment was conducted to study the effect of nitrogen (N), phosphorus (P) andpotash (K) on growth, seed yield and quality of fennel at the vegetable research farm,Department of Vegetable Science, Chaudhary Charan Singh Haryana Agricultural University,Hisar during 2002-2003 and 2003-2004. The experiment consisted of 16 treatment combinationswith four levels each of N (25, 50, 75&100 kg ha-1), P (25&50 kg ha-1) and K (25&50 kg ha-1).The experiment was laid out in randomized block design with three replications. The resultsrevealed significant differences in growth and yield parameters among the treatments.Application of N at 100 kg ha-1, P at 50 kg ha-1 and K at 50 kg ha-1 recorded the maximumvalues of plant height, flowering, umbels per plant and umbellets per umbel, while seeds perumbel, seed yield (q ha-1) and harvest index was found maximum at 75 kg nitrogen, 50 kgphosphorus and 50 kg potash per hectare. However a dose of 75 kg N, 50 kg P2O5 and 25 kgK2O per hectare was found economical.